Upaya Meningkatkan Minat Baca Anak Melalui Pemberian Buku Di Rumah Belajar Ceria Pada Masa Covid-19 - Rhut Dear Dwigita; Tuti Atika (Pengelola Jurnal Politeknik Negeri Ketapang, 2022)
Interest in reading needs to be instilled in children from an early age. Childhood is the right time to cultivate habits. The effectiveness begins with introducing letters, learning to spell words and then learning to interpret words in a sentence that has meaning. After children have the ability to read, it is necessary to continue by providing interesting and representative reading materials for children's development. Interesting reading materials can arouse children's interest in reading books, so that they will form reading habits. If the habit of reading is ingrained in children, then when they grow up it will become a necessity in their lives. So that individual habits that are carried out continuously and from generation to generation will be able to create a reading culture among the community. The purpose of this study is to increase children's reading levels and provide insight to children from an early age that reading is something that is actually fun and useful.